Corporate transition pathways from a policy mix perspective - Luke Georghiou (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2025)
The paper explores the strategic role of policy mixes in steering large-scale incumbent firms towards sustainable economic pathways in Europe. The paper acknowledges the critical contribution of start-ups in the sustainability sector but emphasizes the need for a transition among the established firms dominating carbon-intensive industries so as to meet climate neutrality targets. Drawing upon a review of existing policy instruments in the EU and beyond and on the policy mix literature, Georghiou emphasises the complexity of aligning technological innovation, business models, and regulatory frameworks at different governance levels. Principles for a taxonomy of policy instruments and measures are proposed. These highlight the need to supplement supply-side and regulatory interventions with demand-side instruments. Systemic frameworks are needed to embrace the complexity of transition and to ensure that changes in corporate behaviour are embedded. The paper calls for more evaluation to gain a nuanced understanding of policy influences on corporate behaviour and the combination of resources, incentives, capabilities and opportunities needed to support policy frameworks that encourage innovation and the diffusion of green technology, balancing sustainability with growth and employment objectives.
Keywords: 330; Policy Mix; Corporate Sustainability Transition; Green Innovation; Regulatory Frameworks; Systemic Policy Approaches